2020
DOI: 10.1016/j.tmaid.2020.101702
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare workers' and students' knowledge regarding the transmission, epidemiology and symptoms of COVID-19 in 41 cities of Bolivia and Colombia

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 6 publications
0
16
0
3
Order By: Relevance
“…Overall, a total of eight different education initiatives for nursing students have been described ( Downes, 2015 ; Escalera-Antezana et al, 2020 ; Ferranti et al, 2016 ; McNiel & Elertson, 2017 ; Patel et al, 2018 ; Stirling et al, 2015 ; Vizcaya-Moreno et al, 2015 ; Wu et al, 2009 ). Four of these were proactive interventions integrated into the teaching curriculum ( McNiel & Elertson, 2017 ; Patel et al, 2018 ; Vizcaya-Moreno et al, 2015 ; Wu et al, 2009 ), one formed part of a degree programme, although it was introduced in response to an epidemic ( Stirling et al, 2015 ), two were independent courses ( Downes, 2015 ; Ferranti et al, 2016 ) and one involved education symposia on COVID-19 open to both health professionals and students ( Escalera-Antezana et al, 2020 ). In all but one of these initiatives ( Escalera-Antezana et al, 2020 ) it is specified that the content of education was based on the response guidelines of the USA Centers for Disease Control and Prevention (CDC) and/or those of the Ministry of Health of the country in question, and in all cases the participants included experts in zoonosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, a total of eight different education initiatives for nursing students have been described ( Downes, 2015 ; Escalera-Antezana et al, 2020 ; Ferranti et al, 2016 ; McNiel & Elertson, 2017 ; Patel et al, 2018 ; Stirling et al, 2015 ; Vizcaya-Moreno et al, 2015 ; Wu et al, 2009 ). Four of these were proactive interventions integrated into the teaching curriculum ( McNiel & Elertson, 2017 ; Patel et al, 2018 ; Vizcaya-Moreno et al, 2015 ; Wu et al, 2009 ), one formed part of a degree programme, although it was introduced in response to an epidemic ( Stirling et al, 2015 ), two were independent courses ( Downes, 2015 ; Ferranti et al, 2016 ) and one involved education symposia on COVID-19 open to both health professionals and students ( Escalera-Antezana et al, 2020 ). In all but one of these initiatives ( Escalera-Antezana et al, 2020 ) it is specified that the content of education was based on the response guidelines of the USA Centers for Disease Control and Prevention (CDC) and/or those of the Ministry of Health of the country in question, and in all cases the participants included experts in zoonosis.…”
Section: Resultsmentioning
confidence: 99%
“…Four of these were proactive interventions integrated into the teaching curriculum ( McNiel & Elertson, 2017 ; Patel et al, 2018 ; Vizcaya-Moreno et al, 2015 ; Wu et al, 2009 ), one formed part of a degree programme, although it was introduced in response to an epidemic ( Stirling et al, 2015 ), two were independent courses ( Downes, 2015 ; Ferranti et al, 2016 ) and one involved education symposia on COVID-19 open to both health professionals and students ( Escalera-Antezana et al, 2020 ). In all but one of these initiatives ( Escalera-Antezana et al, 2020 ) it is specified that the content of education was based on the response guidelines of the USA Centers for Disease Control and Prevention (CDC) and/or those of the Ministry of Health of the country in question, and in all cases the participants included experts in zoonosis. The duration of education programmes varied considerably, from a pre-recorded 10-min session ( Patel et al, 2018 ), through courses lasting 3–5 h ( Escalera-Antezana et al, 2020 ; McNiel & Elertson, 2017 ; Vizcaya-Moreno et al, 2015 ) or a full day ( Downes, 2015 ; Ferranti et al, 2016 ), to a 16-h programme split into one-hour sessions ( Wu et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…Escalera-Antezana et al [ 49 ] in their cross-sectional study researched knowledge of COVID-19 symptoms (amongst others) with a one question-item. The research was undertaken in Colombia and Bolivia, employing 1165 healthcare students and workers.…”
Section: Discussionmentioning
confidence: 99%
“… It provides an in-depth insight of research referring to young people’s self-assessed knowledge regarding the symptoms of COVID-19, an understudied topic too. Specifically, only three peer-reviewed academic research papers were found that examine young peoples’ knowledge of COVID-19 [ 47 , 48 , 49 ]. In these three papers, the majority used a sample of university students, drawn from health care and non-healthcare areas of study.…”
Section: Introductionmentioning
confidence: 99%
“…With the vast majority of them being digital natives, most get their knowledge via online platforms and social media [59]. In addition to that, it was shown that focused training courses (held offline before, and online after lockdown) could significantly enhance the knowledge about Covid-19 [85] and that there was no difference in quality between instructor-led and video lesson based instruction on PPE [86]. Local solutions like the 1-sided 'Quick sheet' amongst residents was soon be adopted by the whole department [67] and may also be a valuable transferable solution to other departments.…”
Section: Clinical Knowledgementioning
confidence: 99%